ANTIKINIO MĄSTYMO VISUMIŠKOJO SUBJEKTO DIFERENCIACIJA. - JANKAUSKAS, SKIRMANTAS (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2026)
Early philosophising was holistic in nature, as was the subject matter - the soul. The Sophists began to differentiate this way of thinking by solving a different problem of the era. Recognising the challenges posed by Solon's legal reforms, they began to address the constraints on the initiative of the free citizen of antiquity. To devalue the most significant obstacle - belief in the gods - the Sophists adopted the theoretical approach to fundamental entities outlined by Xenophanes and the Eleatic philosophers. Analysis of the surviving testimonies of Gorgias' work demonstrates that he primarily devalued generally conceivable entities, and therefore potentially the gods implied by them. Distancing himself from the devalued aspect of holistic thinking, Gorgias focused on the remaining aspect and, having analysed its cognitive specificity, developed a personal approach to sensual thinking. Protagoras completed the Sophists' differentiation of holistic thinking, defining the implicit subject of the aspect singled out by the Sophists. Protagoras' 'measure of man' was simply a definition of the subject of everyday thinking, which legitimised the importance of private opinion, i.e. 'δόξα'. Since everyday thinking serves unstoppable human experience, once realised, its subject became an irrevocable point of reference for revising ancient thinking.